2009
DOI: 10.1038/ajg.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

The Vexed Relationship Between Clostridium Difficile and Inflammatory Bowel Disease: An Assessment of Carriage in an Outpatient Setting Among Patients in Remission

Abstract: Detection of C. difficile is increased in IBD outpatients in remission, and strain diversity is consistent with community acquisition from a multitude of sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 35 publications
2
133
0
3
Order By: Relevance
“…Recent reports suggest a high prevalence of CDI in asymptomatic IBD patients. Clayton et al (34) in a retrospective study including 64 patients with UC and 58 with CD, all in clinical remission and without recent exposure to antibiotics, corticosteroids, immunomodulatory drugs or recent hospitalization, found that that the frequency of toxigenic C. difficile was higher in IBD patients than in healthy volunteers (8.2 vs. 1.0%; p=0.02), which is consistent with community-acquired infection.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Recent reports suggest a high prevalence of CDI in asymptomatic IBD patients. Clayton et al (34) in a retrospective study including 64 patients with UC and 58 with CD, all in clinical remission and without recent exposure to antibiotics, corticosteroids, immunomodulatory drugs or recent hospitalization, found that that the frequency of toxigenic C. difficile was higher in IBD patients than in healthy volunteers (8.2 vs. 1.0%; p=0.02), which is consistent with community-acquired infection.…”
Section: Introductionmentioning
confidence: 52%
“…Schneeweiss et al (36) found that corticosteroid initiation tripled the risk of CDI among the IBD patients (relative risk 3.4, 95% CI 1.9-6.1), while no such association with the initiation of immunomodulators or biologics (infliximab) was found. Biological agents (e.g., infliximab, adalimumab) are not associated with increased risk of CDI in IBD patients (36), nor is the use of aminosalicylates (34). PPI use in non-IBD patients has been suggested to increase the risk for CDI (6), but other studies did not find any association between PPI use and CDI in IBD patients (10).…”
Section: Risk Factorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Several studies have linked acute bacterial enteritis with the onset or exacerbation of UC with causative agents including but not exclusively, Clostridium difficile, 11,105,106 Yersinia enterocolitica, 107,108 Campylobacter jejuni 109 and Salmonella spp. [109][110][111][112] It has been suggested that infection…”
Section: Ulcerative Colitis and Bacteriamentioning
confidence: 99%
“…Furthermore, reduced expression of human alpha-defensins in IBD patients may also play a role. 125 Since asymptomatic carriage of C. difficile exists in IBD patients 105 the main practical implication is that all patients with relapse of IBD should have a fecal sample checked for C. difficile, especially those receiving immunosuppressant therapy since this is known to be a risk factor for infection.…”
Section: Ulcerative Colitis and Bacteriamentioning
confidence: 99%